Durable Self‐Healing Superhydrophobic Coating with Biomimic "Chloroplast" Analogous Structure. Issue 15 (9th June 2016) - Wang, Huaiyuan; Liu, Zhanjian; Zhang, Xiguang; Lv, Chongjiang; Yuan, Ruixia; Zhu, Yanji; Mu, Liwen; Zhu, Jiahua
Abstract : An analogous "Chloroplast" structure has been successfully replicated in a graphene/SiO2 composite by dopamine self‐polymerization and in situ growth of nano‐SiO2 on graphene surface. The healing agent of POTS was stored in the analogous "Chloroplast" structure by both chemical bonding and physical absorption. This unique structure enables a superhydrophobic PVDF/RGO‐SiO2 ‐POTS coating with excellent self‐healing capability, durability, and drag reduction performance.